Hermes : god of travels and trade - Temple, Teri.; Squier, Robert (Mankato, MN : Child's World, 2013)
An introduction to Greek mythology that shares the stories and myths about the Greek god Hermes, god of travels and trade.
Includes bibliographical references (p. 32) and index.
Library Media Connection
Library Media Connection, May 2013
4.3
3-6.
3-6
Keywords: Hermes (Greek deity) -- Juvenile literature; Mythology, Greek -- Juvenile literature; Hermes (Greek deity); Mythology, Greek; Greek mythology; Hermes (Greek deity)